The animals - Wee, Mark Nai De (2014)
“THE ANIMALS” is a stop motion animated short film, inspired by the life of Joseph Merrick, the famed Elephant Man, who lived in Britain during the Victorian Era. Merrick exhibits himself as a freak in penny gaffe shows for a meagre mean of living when a serendipitous turn of events changes his life.